Pengaruh ULTAJAS (Ular Tangga Jajanan Sehat) Terhadap Peningkatan Pengetahuan Anak Tentang PJAS (Pangan Jajanan Anak Sekolah): Pengaruh ULTAJAS (Ular Tangga Jajanan Sehat) Terhadap Peningkatan Pengetahuan Anak Tentang PJAS (Pangan Jajanan Anak Sekolah) - Amanah, Siti Nur; Nurul Rohimah, Sri; Siti Sopiah, Sopa; Inayah, Ade; Fitri, Amelia; Sumiyati Salsabila, Siti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Abstract Introduction: PHBS is very easy to say but is it easy to do if implemented? According to Diana 2013 PHBS is difficult to implement because it requires awareness and seriousness about the importance of maintaining health. PHBS is an effort to provide a learning experience that creates conditions for individuals, families and groups by opening lines of communication, providing information and conducting useful education to increase knowledge and attitudes regarding clean and healthy living behavior through approaches, atmosphere building and community empowerment. Health education is very important for children, especially school-age children because at that age children will learn directly from their school environment. Therefore, it is important for school children to know about clean and healthy living behaviors about consuming healthy snacks. Through snakes and ladders games, children are able to develop their motor skills, are able to know themselves, work together with friends, are able to recognize emotions and are more disciplined. Meanwhile, through healthy snacks, children's knowledge increases about healthy and unhealthy snacks, is able to save money not to snack on healthy snacks. not good, children will be more careful in snacking at school and children will focus more on bringing the provisions given by their parentsObjective : The purpose of this health education activity is to increase children’s knowledge about healthy and nutritioous snacks and to make efforts to reduce the poor nutritional status of healthy and unhealthy snacks in Karangpaningal Village, Bojongnangka Hamlet, Panawangan Ciamis. Method: Health education methodology that includes self-health. Participants in this consultation are expected to be able to implement a comprehensive strategy, especially in creating new behaviors, especially PHBS, in the school and community environment. Result: From the results of the study it can be concluded that before delivering the health consultation material as many as 2 people (0.3%) were able to answer questions before the material was delivered, 3 people (0.5%) did not know. Participants did not know about healthy snacks, 1 person (0.2%) participants did not know, participants did not know about healthy snacks. After health counseling, the knowledge of PHBS healthy snack participants increased 100% to 6 people. Conclusion: Expanding knowledge about healthy snacking is a great start for teaching clean and healthy living habits in everyday life. After knowing the characteristics of unhealthy snacks and the dangers of unhealthy snacks, it is hoped that children will stop buying unhealthy snacks.